Reinventing Christian doctrine: retrieving the law-gospel distinction - Wisse, Maarten (T&T Clark, 2022)
"Providing an alternative to current Trinitarian and Christocentric approaches to dogmatics, this open access book instead centres the Augustinian and classical Reformation Law-Gospel distinction. Maarten Wisse demonstrates the viability of dogmatics based on the Law-Gospel distinction from both a historical and a systematic-theological perspective. From a historical perspective, Wisse shows that the actual use of Scripture should be understood as the interplay between a critical concern about the difference between God and the world on the one hand, and the witness to God's presence in Christ in the world on the other. From a systematic-theological perspective, the benefits of approaching dogmatics through the dynamics between Law and Gospel is exemplified by discussions of key dogmatic topics, such as the doctrine of Scripture, predestination, atonement, the Eucharist and the theology of religions. The eBook editions of this book are available open access under a CC BY-NC-ND 4.0 licence on bloomsburycollections.com. Open access was funded by Protestant Theological University"--